2018
DOI: 10.11113/ijbes.v5.n3.267
|View full text |Cite
|
Sign up to set email alerts
|

Step by step approach for qualitative data analysis

Abstract: The application of qualitative techniques is increasing and acceptable among the researchers. However, majority of the researchers and postgraduate students did not consider the importance of giving detailed procedures in qualitative data analysis for better understanding of the qualitative results. There is a need to uncover step by step approach in qualitative analysis for better application of qualitative techniques. This article presented a detailed step-by-step approach for qualitative analysis with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 20 publications
1
53
0
6
Order By: Relevance
“…The assumption was made that enterprises that obtain results should be purposefully selected. In doing so there is need to uncover step by step approach in qualitative analysis for better application of qualitative techniques [12] While primary data were collected empirically through field observations and in-depth interviews to gather information from respondents as key informants. Key informants are selected based on the full authority given by residents as spokespersons regarding the ins and outs of socio-preneurs activities that are empowered in the fields of education, economy, agriculture and the environment by business actor in Bogor, Depok and Jakarta.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption was made that enterprises that obtain results should be purposefully selected. In doing so there is need to uncover step by step approach in qualitative analysis for better application of qualitative techniques [12] While primary data were collected empirically through field observations and in-depth interviews to gather information from respondents as key informants. Key informants are selected based on the full authority given by residents as spokespersons regarding the ins and outs of socio-preneurs activities that are empowered in the fields of education, economy, agriculture and the environment by business actor in Bogor, Depok and Jakarta.…”
Section: Methodsmentioning
confidence: 99%
“…According to Indonesia government strategy, the development of social enterprise enriched by utilizing social capital (local institution such as co-operatives) and local champions in order to handle socioeconomic problems, especially poverty related to cultural factors and limited business opportunities. The government strategy also includes other plans to foster economic growth through strengthening the agriculture, fisheries and mining sectors and manufacturing industries; modernising the services sector; encouraging the mastery of science, technology and innovation; maintaining fiscal sustainability; increasing the competitiveness of non-oil and gas export products and MSMEs; and improving the quality of employment opportunities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Data coding is defined as the procedure of classifying texts to form explanations and broad themes in the data (Creswell, 2007). According to, Creswell (2007) cited by Akinyode and Khan (2018), the thematic analysis aims to explore and understand a subject or the denotation of an idea.…”
Section: Methodsmentioning
confidence: 99%
“…Using level 1 of Kirkpatrick's model, [2,3] results revealed that tutorials are a less formal support strategy where interactive and friendly games were used to make learning interesting for nursing students. Participants indicated that individualised attention and small-group discussions were approaches to learning that clarified concepts.…”
Section: What Were the Lessons Learnt (Outcomes)?mentioning
confidence: 99%